Monitoring the Future: A Continuing Study of American Youth (12th-Grade Survey), 1996 - Bachman, Jerald G. ([Verlag nicht ermittelbar], 1998)
This is the 22nd annual survey in this series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students are randomly assigned to complete one of six questionnaires, each with a different subset of topical questions but all containing a set of "core" questions on demographics and drug use. There are about 1,400 variables across the questionnaires. Drugs covered by this survey include tobacco, alcohol, marijuana, hashish, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), quaaludes, barbiturates (tranquilizers), cocaine, crack, and heroin. Other items include attitudes toward religion, parental influences, changing roles for women, educational aspirations, self-esteem, exposure to sex and drug education, and violence and crime -- both in and out of school.